Effect of Sulfur Supplementation on in vitro Fermentability and Degradability of Ammoniated Rice Straw - Zain, Mardiati; Jamarun, N.; Nurhaita (Pakistan Journal of Nutrition, 2010)
In vitro studies were conducted to determine effect of supplementation various amount of sulfur (Ammonium sulphate) on fermentability and degradability of ammoniated rice straw. The in vitro experiment was carried out following the first stage of Tilley and Terry method. The treatments consisting of four levels of sulfur, were A = ammoniated Rice Straw (RS) (control), B = A + 0.15% Sulfur (S) supplement, C = A + 0.3% Sulfur supplement and D = A + 0.45% sulfur supplement on dry matter. Completely randomized design was used as the experimental design and differences among treatment means were examined using Duncan multiple range test. Variables measured were Ammonia (NH3) and Volatile Fatty Acid (VFA) concentrations, as fermentability indicators, as well as degradability indicators including degradability of Dry Matter (DM), Organic Matter (OM), Neutral Detergent Fibre (NDF), Acid Detergent Fibre (ADF) and cellulose. The results indicated that fermentability and degradability of diets consisting ammoniated RS with Sulfur supplementation were significantly higher than the control diet (p